Possibility of developing low-carbon industries through urban symbiosis in Asian cities - Fujii, Minoru (Animo Repository, 2016)
Energy and resource consumption has been expanding quickly with the rapid growth of Asian cities, which has resulted in increased greenhouse gas emission and waste generation. The promotion of low-carbon industries is an urgent global issue that extends to Asia as well. To reduce carbon dioxide emission substantially, industries must not only introduce energy-saving technologies but also use low-carbon raw materials and fuel, such as recyclable wastes and carbon-neutral biomass. This paper presents the concept of a "hybrid industry," that is, an industry whose processes utilize not only fossil resources but also recycled and renewable resources as much as possible. This study examines the feasibility of hybrid industries through the promotion of urban symbiosis in cities in three Asian countries with different circumstances: Kawasaki in Japan, Ulsan in Korea, and Shenyang in China. Asian cities are in the midst of shifting from dumping wastes to incineration. However, in view of the carbon reduction effect of recycling as well as the cost for recycling and appropriate treatment of wastes, the potential of hybrid industries that use combustible municipal wastes as input should be considered. In this study, the potential for carbon dioxide reduction as well as the costs of promoting hybrid industries are evaluated. The results highlight that promoting hybrid industries generates significant environmental benefits for the three cities, and there are important factors that affect the cost-effectiveness of hybrid industries, including the spatial density of waste generation, composition of wastes, relative labor cost for collection and pre-treatment of wastes compared with construction cost of an incinerator and avoided costs through product and fossil resource substitution, and the willingness of citizens to separate wastes. Finally, key drivers for promoting hybrid industries through urban symbiosis in Asian cities are discussed. © 2015 Elsevier Ltd.